2016
DOI: 10.1038/nprot.2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Using single nuclei for RNA-seq to capture the transcriptome of postmortem neurons

Abstract: A protocol is described for sequencing the transcriptome of a cell nucleus. Nuclei are isolated from specimens and sorted by FACS, cDNA libraries are constructed and RNA-seq is performed, followed by data analysis. Some steps follow published methods (Smart-seq2 for cDNA synthesis and Nextera XT barcoded library preparation) and are not described in detail here. Previous single-cell approaches for RNA-seq from tissues include cell dissociation using protease treatment at 30 °C, which is known to alter the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
331
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(350 citation statements)
references
References 36 publications
5
331
0
1
Order By: Relevance
“…Single-nucleus RNA-sequencing (variously referred to as snRNA-seq, sNuc-seq, Div-Seq, DroNc-seq) has its challenges in that nuclear RNA is less abundant than cellular RNA, and includes precursor RNAs containing introns in various stages of processing. However, results similar to whole-cell RNA-seq have recently been reported, indicating that single-nucleus RNA-seq is a viable alternative for many experimental designs (Habib et al, 2017; Habib et al, 2016; Krishnaswami et al, 2016; Lacar et al, 2016; Lake et al, 2016). Work will need to be done to harmonize human data with data from mouse and other species where fresh tissue and whole cell RNA-seq will be performed.…”
Section: Single-cell Transcriptomicsmentioning
confidence: 77%
“…Single-nucleus RNA-sequencing (variously referred to as snRNA-seq, sNuc-seq, Div-Seq, DroNc-seq) has its challenges in that nuclear RNA is less abundant than cellular RNA, and includes precursor RNAs containing introns in various stages of processing. However, results similar to whole-cell RNA-seq have recently been reported, indicating that single-nucleus RNA-seq is a viable alternative for many experimental designs (Habib et al, 2017; Habib et al, 2016; Krishnaswami et al, 2016; Lacar et al, 2016; Lake et al, 2016). Work will need to be done to harmonize human data with data from mouse and other species where fresh tissue and whole cell RNA-seq will be performed.…”
Section: Single-cell Transcriptomicsmentioning
confidence: 77%
“…There are, however, reliable and reproducible protocols for isolating single neuronal nuclei from frozen postmortem human brain[36,37]. Fortunately, the nucleus contains a significant amount of messenger RNA, and several studies have now demonstrated single-nucleus RNA sequencing[3840]. Lake et al have taken this approach for scRNA-seq–based cell type classification in the human cerebral cortex, identifying 16 neuronal subtypes – 8 excitatory and 8 inhibitory[34].…”
Section: The Cerebral Cortex: the Ultimate Cell Type Diversity Challengementioning
confidence: 99%
“…Also, for some disorders such as autism and schizophrenia, connectivity between brain regions may be of primary importance, rather than specific regional states [18]. Therefore, an argument for tissue specificity should really be cast as an argument for brain region—and cell type—specificity, and current approaches to brain epigenetic measurement are only beginning to reach this granularity [19, 20]. With respect to cell type, a portion of epigenomic marks are known to be cell-type specific, and the brain is a heterogeneous mix of neurons and glia, including astrocytes, oligodendrocytes, and microglia.…”
Section: Introductionmentioning
confidence: 99%